Status keberlanjutan keramba jaring apung di Danau Rawa Pening pada dimensi ekologi berdasarkan pendekatan RAPFISH - Kinanti, Tesalonika Putri; Djohan, Djohan; Cahyaningrum, Desti Christian (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2025)
Floating net cages (KJA) aquaculture is an important livelihood source for local community, but it also contributes to eutrophication in Rawa Pening Lake. So, it is necessary to ensure that KJA management is carried out based on the sustainable development principles to minimize the environmental impacts. This study aims to assess the sustainability status of KJA management in Rawa Pening Lake from the ecological dimension. Data were collected through interviews, direct observation, direct measurement and literature study based on following attributes; water quality, water fertility, environmental conditions, biosecurity and fish health. Then, data that has been scored were analyzed by Multi-Dimensional Scaling (MDS) using the RAPFISH application embedded in Ms. Excel). The results showed the KJA sustainability index is 49,567 (poor sustainability category). The most significant attribute of KJA sustainability is water nutrient content, i.e. N:P ratio (leverage = 4,129). It is concluded that the management of KJA in Rawa Pening Lake has been not carried out based on sustainable aquaculture management principles. Therefore, management strategies focusing on controlling water nutrient levels are urgently required to ensure the sustainability of KJA in Rawa Pening Lake.